Willingness to pay for agricultural mechanization services by smallholder farmers in Malawi - Tufa, Adane H.; Alene, Arega D.; Ngoma, Hambulo; Marenya, Paswel Phiri; Manda, Julius; Md Abdul Matin; Thierfelder, Christian L.; Chikoye, David (Wiley, 2024)
One of the main barriers to adopting smallholder agricultural mechanization in developing countries is the mismatch between the economies of scale of machines and farm size. Private sector-led mechanization services hold a promise to address this challenge, but there is a lack of evidence on demand for smallholder mechanization services. This study estimates the farmers' willingness to pay for mechanization services using the double-bounded contingent valuation method and data from 1512 households. Results show that, on average, farmers are willing to pay 11%, 33%, and 5% more than prevailing market rates for land preparation, maize shelling, and transportation services, respectively. The amounts farmers are willing to pay for the mechanization services vary by sex, age group, size of cultivated land, the value of farmer assets, market access, and agroecology. Men are willing to pay 26%, 25%, and 11% more than women for land preparation, maize shelling, and transportation services. Moreover, 40% of female and 90% of male farmers are willing to pay more than or equal to the prevailing market rate for land preparation services. The high demand for mechanization services among smallholder farmers points to the need for making the machinery available to rural communities through mechanization service providers or machinery hiring centers run by the private sector. The paper concludes by discussing the contextual factors and policy options for promoting smallholder mechanization in Malawi. [EconLit Citations: O33, Q11, Q13, Q16].